Hematopoietic Stem Cell Transplantation in Inborn Errors of Metabolism - Tan, Emily Y.; Boelens, Jaap Jan; Jones, Simon A.; Wynn, Robert F. (Frontiers in Pediatrics, 2019)
Haematopoietic stem cell transplantation (HSCT) has been established as an effective therapy for selected inborn errors of metabolism. The success of HSCT in metabolic disease is best exemplified through the treatment of Hurler’s syndrome, a lysosomal storage disease. Through the collaborative effort of several international centres, factors that predict successful patient and transplant outcomes have been identified. In this review, we discuss the principles that underlie the use of HSCT in metabolic diseases. We consider the clinical indications, conditioning regimens and disease-specific follow-up for HSCT in different metabolic diseases. We highlight persisting challenges in HSCT to delay progression of certain organ systems that remain refractory to HSCT and the relatively high rates of aplastic graft failure. Finally, we evaluate the variable applicability of these principles to other inherited metabolic disorders including peroxisomal, mitochondrial and other lysosomal storage diseases.